Creative brand launch in phamaceutical over-the-counter markets – case Burana - Ylivakeri, Eeva-Liisa (My University, 2013)
The purpose of this study is to examine how a launch of a pharmaceutical over-the-counter sold (OTC) brand can be done by using creative solutions and thus affecting the product life cycle. The study is inspired by a phenomenon called Burana. The Burana brand has been a market leader of OTC painkillers in Finland for the past 27 years. The aim of this study is to “solve the mystery” behind Burana brand’s success by focusing on the launch phase of Burana as an OTC medicine. Farmos Group Ltd (the owner of the brand in 1980´s) had not originally invented the product in question – ibuprofen – and the product had already reached it´s maturity phase, if not even decline from the product life cycle aspect when this phenomenon takes place. This has made the marketing choices, the product launch phase as well as the product management even more interesting from the company point of view as well as from a learning point of view. The methodology in this study is qualitative with a descriptive research strategy, while the study is conducted as a longitudinal single-case study. The methods used in this study have been collecting, analyzing and interpreting the data, which is based on the interviewees’ comments and observed behavior. According to the study, the successful launch phase helped in setting the product one step ahead of the competitors and thus aided the brand leadership and prolonged the product life cycle. Another notable aspect that became clear from the interviews and the documentary of Burana´s launch phase was the innovative idea of involving the people of the distribution chain into the product launch through education. As this study has pointed out, it is not enough to for a company to build an innovative team of employees, but also to offer them an involved and encouraging management. According to the interviews, the support from the company management gave the marketing team the encouragement to be innovative. It can be thus stated that the management of a company has an essential role in fostering the creativity within the company.